Metabolic reprogramming of breast tumor associated macrophages - Dias, Ana Sofia Santos (2024)
Breast cancer (BC) is a complex and heterogeneous disease that poses a significant global health challenge. While advancements in early detection and treatment modalities have improved patient outcomes, challenges persist, particularly in addressing the aggressive and resistant nature of certain breast cancer subtypes. One promising avenue of research involves understanding and targeting the tumor microenvironment (TME) to develop more effective therapeutic strategies. Tumor-associated macrophages (TAM) are the predominant stromal cells in the breast TME and the abundance of pro-tumoral M2-like TAM correlates with unfavorable pathological and clinical features. Hence, shifting TAM polarization toward an M1-like anti-tumoral phenotype is an attractive strategy to elicit tumor regression and aid cancer treatment. The functional features of macrophages are intricately linked to their metabolism, with distinct metabolic programs of M1- and M2-like macrophages providing a sound rationale for exploring the therapeutic potential of macrophage modulation via metabolic reprogramming. In this work, we have employed an untargeted metabolomics approach to provide a comprehensive view of metabolic adaptations involved in the pro-tumoral TAM phenotype and its modulation by drugs targeting metabolic pathways. Initially, we established and characterized an in vitro model of tumor-educated macrophages (TEM). THP-1-derived macrophages were incubated in media conditioned by BC cells – specifically, the non-metastatic MCF-7 cell line, representative of the luminal A subtype, producing MCF-TEM; and the metastatic MDA-MB-231 cell line, representative of the highly aggressive triple negative breast cancer (TNBC) subtype to generate MDA-TEM. Employing NMR profiling of culture medium (exometabolomics) and of cell extracts (endometabolomics), we unveiled the metabolic adaptations of TEM, coupled with phenotypic characterization through qP CR and ELISA assays. Our findings suggested that TEM utilize alternative substrates, such as alanine, pyruvate and branched chain α-keto acids (BCKA) to compensate for shortages in glucose and glutamine within the conditioned media. Remarkable alterations in intracellular metabolic pathways were observed, including polyamine catabolism in MDA-TEM, collagen degradation in MCF-TEM and changes in adenosine metabolism, mainly in MDA-TEM. TEM also exhibited shifts in lipid composition, reflecting lipid droplet accumulation, cholesterol efflux, and membrane remodeling. Interestingly, following a second-stage incubation in fresh RPMI medium, TEM still displayed several metabolic differences compared to control macrophages (M0), which underscores the lasting impact of the BC cells-conditioned environment on macrophage behavior. In a subsequent stage, using the established in vitro model of MDATEM, we evaluated a selection of metabolic drugs (MDs) targeting different metabolic pathways. To assess their ability to skew the MDA-TEM phenotype towards an anti-tumoral state, we quantified the production of the pro-angiogenic factor VEGF and the well-established anti-cancer pro-inflammatory cytokine TNF-α. Dichloroacetate (DCA), 6-Aminonicotinamide (6-AN) and Etomoxir decreased VEGF secretion and enhanced the release of TNF-α, while significantly modulating the metabolome of TEM. Specifically, DCA induced the downregulation of glycolysis and consumption of extracellular lactate, glutamate and a-keto-b-methylvalerate, concomitant with the secretion of short chain fatty acids. Additionally, DCA reconfigured lipid metabolism by decreasing triglycerides and increasing cholesterol, showing a strong correlation with heightened TNF-α production in response to pro-inflammatory stimulation. The inhibition of the pentose phosphate pathway by 6-AN was accompanied by enhanced glutaminolysis, in contrast with glutamine release in untreated TEM. Notably, glutamine utilization exhibited a high correlation with the decrease in VEGF production. In the case of Etomoxir-treated TEM, compensation for inhibition of fatty acid oxidation occurred through the upregulation of glycolysis, accompanied by the catabolism of intracellular amino acids and increased consumption of extracellular BCKA and citrate. Altogether, the integration of exo- and endometabolomics elucidated how in vitro generated TEM reprogrammed their metabolism and phenotype in response to: i) the metabolic milieu imposed by distinct BC cells; ii) three metabolic drugs (DCA, 6-AN, and Etomoxir) that attenuated the pro-tumoral state of MDA-TEM. This comprehensive approach has unveiled several metabolites and metabolic pathways with potential immunoregulatory roles, thereby extending current understanding of the metabolism-phenotype axis in TEM.